THE INFLUENCE OF READING, MIND MAPPING, AND SHARING (RMS) LEARNING MODELS ON RESULTS OF LEARNING SCIENCE IN STUDENTS OF CLASS V SDN WERDOYO GROBOGAN - Azizah Thalib; Kristiyanti Kristiyanti (Jurnal Dikdas, 2019)
This research aims to determine whether there is an effect of the Reading, Mind Mapping and Sharing (RMS) learning model on the learning outcomes of Natural Sciences in students of Class V SDN Werdoyo, Godong, Grobogan. This type of research is a quasi experimental design in the form of nonequivalent control group design. The study population was all students at Class V SDN Werdoyo and students Class V at SDN 3 Latak. The sample amounted to 62 students. Data collection techniques with tests and  questionnaire. Hypothesis testing uses the t-test formula. The results showed that: RMS learning models affect the learning outcomes of  Natural Sciences in students of Class V SDN Werdoyo. This can be seen by the significant difference in the cognitive learning outcomes of science between the experimental group applying the RMS learning model and the control group with the learning that is usually done by the teacher, namely the conventional model. This is indicated by the value of sig t-test smaller than α. (0,000 <0.05). The average result of the post test score of the experimental group was 89.4 higher than the average result of the post test value of the control group that was 66.1.